FORMATION OF LITHOFACIES PRECONDITIONS IN NEWLY FORMED TECHNOGENIC COLLECTORS LVIV-VOLYN COAL-GAS BASIN - Лівенцева, Г. А. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The studies conducted have revealed possible litho-facies composition of the man-made reservoirs in the coal seams mined out within the gas-bearing Lviv-Volyn coal basin where sedimentary rocks of the Lower Carboniferous, Tournaisian, Visean, Serpukhovian and lower part of Middle Carboniferous formations occur. They are represented by crushed shales, siltstones, sandstones, limestones and carbonaceous remains in the of the coal rock sequence. Conglomerates and gravelstones make only 0.25% of coal-bearing formation to form thin (0.2-1.5, occasionally to 3-4 meters) lenses. Gravel sandstones have a limited distribution, making lenses and interbeds of 0.5-1.5 m thick. The sandstones are composed by fine-, medium- and coarse-grained types. Siltstones are of dark gray color, often caused by clay and carbonaceous minerals. The most typical shales are composed by finely dispersed material with silty admixture, limited carbonaceous and calcareous varieties. Their dark, mostly gray color is due to the presence of humus or sapropel material. Limestones are grey, dark grey, sometimes with a brown tint; they are usually fine- or medium crystalline, often with re-crystallized areas. Coal is mostly of humus type, the sapropel occurs occasionally in the form of interbeds, mainly in the top and bottom humic layers. Coal is dense, viscous, black and black and gray in color. The core set of the coal rock massif taken from well #7427, located in the northern part of the Lubel coal field, is well represented in the geological section. The upper alluvial-limnic-swampy-lagoonal coal-bearing sub-formation (middle part) consists of four litho-cycles of the higher order (first one is a lagoon-marine transgressive; the second one is a marine-lagoon regressive; the third one is an uniformly lagoonal, and fourth one is a lagoon-marine transgressive cycle) with one another of lower order, the open marine cycle.